Efektivitas Media Wayang Kertas dalam Meningkatkan Keterampilan Berbicara pada Materi Cerita Fantasi di Kelas X MA Nihayatul Amal Purwasari - Fajaralvidens, Awank Zuhud; Nuraini, Cut; Mujtaba, Sahlan (Jurnal Ilmiah Wahana Pendidikan, 2024)
It is undeniable that most young people in Indonesia are less proficient in speaking. Based on this, this study looks at how the effectiveness of paper puppet media in improving speaking skills with a population, namely X grade students of MA Nihayatul Amal Purwasari which amounted to 134 and samples of X MIPA and X IPS which amounted to 67 students. This study uses a quantitative approach with the type of research Quasi Experimental Design which divides the subjects into treatment groups (X MIPA) and control groups (X IPS ). The design in this study used an experimental research design called Posttest Only Control Group Design. Sampling in this study, namely the post-test in the experimental class using puppet media and the control class not using puppet media. The results obtained in this study, namely the existence of a significant influence on students' speaking skills. The average value of the experimental class was 69.71 and the control class was 66.36 and had an average difference of 3.3. To find out how the effectiveness of using paper puppet media in improving speaking skills, a hypothesis test using the t test is used, after the test, the Sig. (2- tailed) of 0.008 is smaller than 0.05. Because the value of Sig. (2-tailed) value is smaller than 0.05 then the hypothesis is accepted